Lignosus rhinocerus (cooke) ryvarden: a medicinal mushroom that stimulates neurite outgrowth in pc-12 cells - Eik, L.F.; Naidu, M.; David, P.; Wong, K.H.; Tan, Y.S.; Sabaratnam, V. (Hindawi, 2012)
A national treasure mushroom, Lignosus rhinocerus, has been used to treat variety of ailments by local and indigenous communities in Malaysia. The aim of this study was to investigate the potential of the most valuable part of L. rhinocerus, the sclerotium, on neurite outgrowth activity by using PC-12Adh cell line. Differentiated cells with one thin extension at least double the length of the cell diameter were scored positive. Our results showed that aqueous sclerotium L. rhinocerus extract induced neurite outgrowths of 24.4% and 42.1% at 20 μg/mL (w/v) of aqueous extract alone and a combination of 20 μg/mL (w/v) aqueous extract and 30 ng/mL (w/v) of NGF, respectively. Combination of NGF and sclerotium extract had additive effects and enhanced neurite outgrowth. Neuronal differentiation was demonstrated by indirect immunofluorescence of neurofilament protein. Aqueous sclerotium extract contained neuroactive compounds that stimulated neurite outgrowth in vitro. To our knowledge this is the first report on neurite-stimulating activities of L. rhinocerus.